2021
DOI: 10.3126/jnspoi.v5i1.38178
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Gingival Pigmentation and its Association with Gingival Biotype and Skin Colour

Abstract: Introduction: The facial appearance depends on several oral and extraoral factors including colour of facial skin and pigmentation of gingival epithelium. The colour of the gingiva varies among individuals and is thought to be associated with cutaneous pigmentation which ranges from light to dark brown or black colour. Objective: To assess the prevalence of physiological gingival pigmentation, gingival biotype and their association with skin colur in Nepalese subjects visiting Kantipur Dental College and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Furthermore, we observed that gingival recession, thin gingival biotype, and inadequate width of attachment were more pronounced in the mandible [ 33 ]. This could explain the robust link between frenal attachment and oral hygiene status in the mandible.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we observed that gingival recession, thin gingival biotype, and inadequate width of attachment were more pronounced in the mandible [ 33 ]. This could explain the robust link between frenal attachment and oral hygiene status in the mandible.…”
Section: Discussionmentioning
confidence: 99%
“…4 Gingival hyperpigmentation is more prevalent in attached gingiva as compared to other parts of gingiva. 3,5 Gingival hyperpigmentation is completely physiological problem in most of the cases. But for some individuals, hyperpigmentation is esthetically unpleasant which is more evident in a patient with gummy smile or high smile line while talking or smiling.…”
Section: Discussionmentioning
confidence: 99%
“…2 Although clinical gingival pigmentation is not a medical problem, hyperpigmented gingiva may cause esthetic problems in patients with a high smile line. 3 To overcome this concern, gingival depigmentation is performed to improve the aesthetic concern of the patient. Treatment plan and selection of technique mainly depend on patient's skin colour, extent of gingival pigmentation, lip line, upper lip curvature, esthetic concern and expectation from the treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Similar prevalence of gingival biotype (75.6% thin, 24.6% thick) was obtained in the mandibular arch but higher prevalence (53.2% thin, 46.8% thick) was discovered in the research done byLee et al [16], as compared to the current study. In contrast, Shao et al[41], Shah et al[42]and Rijal et al[43] discovered greater prevalence of thick gingival phenotype. This difference in gingival thickness in different population may be due to racial variation where Asians usually have a thin gingiva as compared to Caucasians [16,41,44,45].The correlation between the mean WAG and TAH was not seen statistically signi cant in the upper arch (p-value = 0.09), lower arch (p-value = 0.65), and overall (both arches, p-value = 0.29).…”
mentioning
confidence: 94%